Analisis Kebijakan Pajak Bagi Usaha Daur Ulang Sampah - Endang Mahpudin; Reminta Lumban Batu; Zulfa Aulia Nurul Putri; Imam Fadilah (Peneliti.net, 2023)
The waste problem is currently considered one of the most pressing problems. However, despite these environmental problems, there must be ways to address them, and one way to do this is through programs such as the Waste Recycling Industry and the Waste Bank. This study analyzes the most optimal policies for waste handling. This study uses qualitative data in the form of descriptive analysis. Research results reveal that giving incentives to waste management businesses will have a positive impact on all aspects. In terms of economics and business continuity, it will directly increase related business income, due to reduced costs caused by the incentives provided. The incentives provided can be implemented into several types of taxes, such as Value Added Tax and Income Tax, similar to policies that have been implemented in various countries. Indonesia needs to adopt some of these steps in order to boost economic benefits, increase the motivation for recycling waste due to incentives, and indirectly affect the reduction in the amount of waste.